DEVELOPING ESP READING MATERIALS FOR THE ELEVENTH YEAR DRESSMAKING STUDENTS OF VOCATIONAL HIGH SCHOOL - Rosy Maya Deli Samosir; Lidiman S M Sinaga; Tiarnita M S Siregar (Universitas Negeri Medan, 2017)
The Objective of this research were: (1) To develop ERM to meet the needs of second grade of dressmaking students at SMKN 10 Medan, (2) To Design ERM which is suitable to the needs of second grade of dressmaking students at SMKN 10 Medan. The subjects were the eleventh year students of dressmaking department at SMKN 10 Medan. The study was a Research and Development (R & D) study which is adapted from Borg and Gall (1983). This research were conducted by six phases, they are, Gathering information and data, Analyzing data, Designing new reading materials, Validating new reading materials, Revising new reading materials, Revised-developing reading materials. The Instruments for collecting the data were 30 questionarries need analysis and interview students, teacher and practitioner. The results from the data were the students need authentic material which related and appropriate to their need in order they can understand English well. The developed materials were validated by two experts, one is a lecture and the other is a teacher. The validator scored 4 creteria. The research findings showed that the developed materials were appropriate to be implemented. The average score of validation was 4,72 (lecture score) and 4,75 (teacher score). Based on the results of the study, conclusion and suggestions are directed to the teachers and institution who are teaching in SMKN 10 Medan generally to create and to develop the materials based on students need.Key words: English Reading Materials, Vocational High School Students, English for Specific Purpose